Wave Energy Potential, Behavior and Extraction - Li, Hua (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Wave energy has a higher potential than most of the available ocean energy resources; however, it fluctuates dramatically depending on geographical and temporal baselines. The complexity of wave energy is only exacerbated by that fact that the cycle of creation, transport, and disappearance of wave energy is influenced by a wide variety of factors. This Special Issue of Energies explores the latest developments in wave energy potential, behavior, and extraction. This Special Issue introduces 1) thorough reviews on the status of wave energy development, 2) novel technologies to extract wave energy including wave energy converter design, and 3) latest methodologies applied in analyzing wave energy potentials.